(untitled) - Hartley, Bernard (Oxford, 1996)
This book covers the elementary structures and vocabulary of English with emphasis on developing oral skills. The material consists of 80 units, each unit provides a 50-minute lesson and is clearly laid out on a separate page
Keywords: English language,English language; Spoken english,Textbooks for foreign speakers